Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. (BMC plant biology, 2010)
Drought is a common stressor in many regions of the world and current climatic global circulation models predict further increases in warming and drought in the coming decades in several of these regions, such as the Mediterranean basin. The changes in leaf water content, distribution and dynamics in plant tissues under different soil water availabilities are not well known. In order to fill this gap, in the present report we describe our study withholding the irrigation of the seedlings of Quercus ilex, the dominant tree species in the evergreen forests of many areas of the Mediterranean Basin. We have monitored the gradual changes in water content in the different leaf areas, in vivo and non-invasively, by 1H magnetic resonance imaging (MRI) using proton density weighted (rhow) images and spin-spin relaxation time (T2) maps.
From Duplicate 1 ( Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Peñuelas, Josep; Lope-Piedrafita, Silvia )

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
The following values have no corresponding Zotero field: accession-num: 16648953
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.